An Evaluation of Acceptance Level of G-Flex Gas Stimulation Technology Among Rubber Smallholder - Nur Badriyah, Kamarul Zaman (2012)
This research is to study the on factors causing the acceptance gas stimulation technology or the trade name in G-Flex. Development agents such as Malaysian Rubber Board have been conducting various courses and projects for the success of each generic technology are introduced. This study is to identify factors for the acceptance of rubber technology by rubber smallholders, and in this study focused on gas stimulation technology, G-Flex. There are four objectives to achieve in this study. First objective is to identify level of gas stimulation technology practice among rubber tappers, second objective is to identify attitude towards changes, change from conventional tapping practice to new system using gas stimulation technology, G-Flex, third objective is to identify level towards innovation and final objective is to identify the relationship between good relationship with development agent and acceptance of gas stimulation technology, G-Flex. This study used the method of collecting primary data by distributing questionnaires to the smallholders who have applied the G-Flex. Respondents were selected randomly, and data obtained from the primary data have been analyzed quantitatively. This study found that a good relationship with the development agents had a positive relationship with the acceptance of gas stimulation technology, G-Flex. In addition to the practice of the use of proper G-Flex also has a positive relationship with the acceptance of gas stimulation technology, G-Flex. Attitude towards innovation showed a positive relationship with the acceptance gas stimulation technology; G-Flex and the last findings Good Agricultural Practice give positive relation with the acceptance of gas stimulation technology, G-Flex. These studies provide benefit to the various party, the Ministry of Trade and Commodities can formulate longterm strategy to increase productivity, while rubber plantation area will be reduced by the Year 2020. Furthermore, this study also serves to instill the development agent for the information and disseminate information to smallholders to use technology and applied it at the right way. Secondly, it is useful to target groups of smallholders who acts as a measuring stick for the success project conducted.